(untitled) (Biological Sciences - PJSIR, 2001)
Low molecular weight epoxy resin based on diglycidyl ether of bisphenol A was synthesized and mixed at constant percentages with natural rubber. The rubber/epoxy system was cured with various types of curing agents such as ethylene diamine, maleic anhydride as well asthe preparedresole phenolformaldehyde.Astudyof thephoto-induced crosslinking ofthepreparedelasticadhesivesandfilmsampleswascarriedoutbyexposuretoultravioletlamp(300W) for 2 weeks at 20°e. Samples containing ethylene diamine were cured at 2S±1°C for 24 h while samples containing maleic anhydrideor resolephenolformaldehyde resins werethermallycuredat ISO-170°Cfor 10min.Cured adhesive compositions were tested mechanically and physically and evaluated as wood adhesives. While hardness, chemical resistance as wellasheatstabilityofthepreparedcuredfilmsampleswereinvestigated.The obtaineddata indicatethat the highest epoxy resin content and the presence of resole phenol formaldehyde resin in compositions improve the tensile strength and adhesion properties on wood. While their cured film samples have the best hardness properties, chemical resistance andheat stability.